DESTINATION: a phase 3, multicentre, randomized, double-blind, placebo-controlled, parallel-group trial to evaluate the long-term safety and tolerability of tezepelumab in adults and adolescents with severe, uncontrolled asthma - Menzies-Gow, Andrew (Respir Res, 2020)
BACKGROUND: Tezepelumab is a human monoclonal antibody that blocks the activity of the epithelial cytokine thymic stromal lymphopoietin. The efficacy, safety and oral corticosteroid-sparing potential of tezepelumab are being investigated in two ongoing, phase 3, randomized, double-blind, placebo-controlled studies (NAVIGATOR [NCT03347279] and SOURCE [NCT03406078]). DESTINATION (NCT03706079) is a long-term extension (LTE) of these studies. METHODS: DESTINATION is a randomized, double-blind, placebo-controlled LTE study in adults (18–80 years old) and adolescents (12–17 years old) with severe, uncontrolled asthma who are receiving treatment with medium- or high-dose inhaled corticosteroids plus at least one additional controller medication with or without oral corticosteroids. The study population will comprise patients who complete the 52- and 48-week NAVIGATOR and SOURCE studies, respectively. Patients who were randomized to receive tezepelumab 210 mg every 4 weeks (Q4W) in either predecessor study will continue to receive this regimen for 1 year; those who were previously randomized to receive placebo will be re-randomized (1:1) to receive either tezepelumab 210 mg Q4W or placebo for 1 year. Patients will receive their prescribed controller medications throughout DESTINATION and study physicians will have the opportunity to down- or up-titrate dosage of these medications, if appropriate. The primary objective is to evaluate the long-term safety and tolerability of tezepelumab over 104 weeks (inclusive of the treatment period of either predecessor study). The secondary objective is to assess the long-term effect of tezepelumab on asthma exacerbations. Patients recruited from SOURCE will be followed up post-treatment for 12 weeks. Patients recruited from NAVIGATOR who complete 100 weeks of tezepelumab treatment will be eligible for either 12 weeks of follow-up or a 36-week extended follow-up during which the clinical benefit of tezepelumab after treatment cessation will be investigated. DISCUSSION: DESTINATION will evaluate the long-term safety, tolerability and efficacy of tezepelumab versus placebo with continued dosing for up to 2 years. DESTINATION will also evaluate the clinical effect of tezepelumab after treatment cessation. This LTE study aims to elucidate the long-term safety implications of receiving tezepelumab and to assess its potential long-term treatment benefits in patients with severe, uncontrolled asthma. TRIAL REGISTRATION: NCT03706079 (ClinicalTrials.gov). Registered 15 October 2018.